Dampak Patah Hati terhadap Kesehatan Mental Mahasiswa di Era Digital - Nabil (PT. Saha Kreasi Indonesia, 2025)
Heartbreak among students is an emotional phenomenon that significantly impacts mental health, especially in the digital era, which increases exposure to ex-partners through social media. This study uses a qualitative descriptive approach and literature analysis to examine how the experience of heartbreak affects students' mental health in terms of stress, anxiety, depression, decreased motivation, and maladaptive digital behaviors. Findings indicate that the digital era prolongs emotional distress through digital intimacy, algorithm-based exposure, and cyberstalking. This study emphasizes the need for mental health literacy, social support, and regulation of social media use for students.